STUDI PEMANFAATAN TUMBUHAN OBAT TRADISIONAL OLEH MASYARAKAT SUKU OIRATA PULAU KISAR KECAMATAN PULAU-PULAU TERSELATAN KABUPATEN MALUKU BARAT DAYA - Beatrixs Rupilu; Theopilus Watuguly (Program Studi Pendidikan Biologi FKIP Unpatti, 2018)
Background: Medicinal plants are medicinal plants that can relieve pain, increase endurance and treat various diseases. The Oirata tribe is an indigenous tribe of Kisar Island. The community traditionally uses various types of plants as alternative treatments to cure diseases because they are easier to obtain and there are no side effects. Methods: This study uses descriptive methods. Data collection techniques by conducting interviews, observation, questionnaires, and collecting and documenting medicinal plants. Results: Medicinal plants found in the Oirata Tribe of Kisar Island, the Sub district Islands, Southwest Maluku Regency are 31 types of medicinal plants. Plant parts used are roots, bark, leaves, flowers, fruits and seeds. How to process traditional medicinal plants is done by boiling, pounding, chopping, squeezing, pasting, wrapping, heating, and some even eaten directly to swallow the water. Conclusion: The way to use it for the people of the Oirata tribe is that it is single because they do not use plants mixed with plants or other raw materials only mixed with water.